Knowledge, Attitude and Practice Among Dental Professionals Related to Periodontitis and Alzheimer’s Disease - Ruchi Pandey; Radhika Pujara; Priyanka Bansal; Roshni Lekhi; Pooja Palwankar; Lipika Gopal (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontitis is chronic infection and is linked to systemic diseases like Alzheimer’s disease (AD). AD is a neurodegenerative disorder occurring due to accumulation of aggregates of amyloid β peptide and tau proteins. The current study aims to assess the knowledge, attitude, and practice about treating AD cases. Material and Method: Questionnaire-based survey was done on 270 dental professionals and dental students. Data was analyzed using bar chart, and hypothesis was tested using Chi-Square test. Results: There is an association between practical knowledge and attitude among dental professionals and students, but there is lack of practice-based approach for treating Alzheimer’s patients. Conclusion: The dental professionals have knowledge regarding perio-systemic link, but still need to upgrade their understanding toward AD with periodontitis.